Clinical Perspectives - Biologics in IBD: What's All the Fuss? - Hillary Steinhart (Canadian Journal of Gastroenterology)
Up until the present time, agents with relatively nonspecific anti-inflammatory or immunomodulatory effects such as 5-acetylsalicylic acid, corticosteroids and azathioprine have been the mainstay of inflammatory bowel disease medical therapy. These drugs have been quite useful in one or more clinical settings, but they have been hampered by modest efficacy, significant toxicity or both. With greater understanding of the specific pathways of the gut mucosal immune response, it is hoped that newer biologic response modifiers will provide better efficacy, with an improved adverse event profile compared with older existing therapies. This article examines the evidence behind the use of biologic therapies such as anti-tumour necrosis factor-alpha, interleukin-10, interleukin-11, anti-integrin antibody and antisense intercellular adhesion molecule-1 oligonucleotide.